2021
DOI: 10.1521/aeap.2021.33.5.361
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Dapivirine Gel Administered Rectally to HIV-1 Seronegative Adults (MTN-033 Study)

Abstract: We triangulated quantitative and qualitative assessments to evaluate participants’ acceptability of 0.05% dapivirine rectal microbicide (RM) gel administered via two separate modalities (a rectal applicator and an artificial phallus for use as a coital simulation device) as part of a Phase I trial (N = 14) among men who have sex with men (MSM) randomized using a 1:1 ratio. Overall, participants reported favorable acceptability of the gel (n = 11; 78.6%), the same or more at the end of the study compared to whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…effectiveness, mode of delivery, timing of use before sex, duration of protection, side effects). Consistent with prior research [6,7,10,11,19,20,22], we hypothesized that higher HIV prevention effectiveness and the absence of side effects would be the two most important features reported by participants. Second, we examined participants' preferred attributes across the features studied.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…effectiveness, mode of delivery, timing of use before sex, duration of protection, side effects). Consistent with prior research [6,7,10,11,19,20,22], we hypothesized that higher HIV prevention effectiveness and the absence of side effects would be the two most important features reported by participants. Second, we examined participants' preferred attributes across the features studied.…”
Section: Introductionsupporting
confidence: 56%
“…RMs could provide a prevention alternative for people seeking a pericoital prevention modality, as opposed to a systemic PrEP modality [ 7 9 ]. If found to be safe and effective, RMs could be designed to deliver HIV/STI prevention drugs and be behaviourally congruent with users’ lifestyles and contexts [ 1 , 10 , 11 , 12 ]. Enemas, suppositories and fast‐dissolving inserts [ 13 16 ] could be viable rectal delivery modalities given their high hypothetical acceptability as potential RM vehicles [ 13 , 17 , 18 ]; however, the hypothetical nature of these findings may not translate into real‐world acceptability and use.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our hypotheses for our acceptability and adherence endpoints, SGM participants reported high overall acceptability for all three products and high overall adherence per protocol and per RAI act. While survey research literature has noted high hypothetical acceptability to RMs as an HIV prevention strategy prior to RAI [9,14,15,17,20,24,32], there has been limited research exploring the real-world acceptability and adherence of these three products. The absence of these data is troubling from a product development perspective given the increasingly restrictive costs and resources required to empirically evaluate a promising biomedical HIV prevention candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Most rectal microbicide candidates have been formulated as gels because of their similarities to lubricants, highlighting the potential for the rectal microbicide gel to be readily incorporated into users' sexual practices [10,[14][15][16]. While ideal from a behavioral congruence perspective, these gel formulations have required the use of an applicator to achieve sufficient drug delivery, which could present acceptability and adherence challenges for long-term uses [17,18], At this time, it is unclear if topical gels would be able to deliver protective levels of HIV prevention drugs when used without an applicator [15,19,20]. As such, researchers and advocates have argued that other rectal delivery modalities should be considered, including suppositories, fast-dissolving inserts, and enemas [21][22][23].…”
Section: Fundingmentioning
confidence: 99%
“…CAPRISA 004, iPrEx, TDF2, Partners PrEP, VOICE, and FEM-PrEP trials have been conducted using TFV gel (30), though failures have often been traced back to poor adherence. Rectal delivery has also been investigated in the form of gels for safety and acceptability (31)(32)(33)(34)(35)(36) but not as a douche or tested for efficacy. We recently demonstrated that TFV hypo-osmolar (HOsm) douching in rhesus monkeys markedly promotes local drug uptake and faster enzymatic turnover to TFV-diphosphate (TFV-DP) in colorectal tissues compared with iso-osmolar (IOsm) douche formulations, and this delivery yields durable protection against SIV and simian/human immunodeficiency virus (SHIV) infection ex vivo using sequentially collected rectal explants (37).…”
Section: Introductionmentioning
confidence: 99%